PERTANGGUNGJAWABAN HUKUM PELAKU USAHA ATAS IKLAN YANG MENYESATKAN DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Nila Trisna (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
Consumer Protection Against Misleading Advertising in matters relating to advertising activities carried out by mass media players based on the rights and obligations of both parties by taking into account the provisions regarding advertising and analyzing it based on Law Number 8 of 1999 concerning Consumer Protection. Efforts to protect consumers must first be done through law. Legal regulations must be created to protect consumers and the responsibilities of businesses or producers. The Consumer Protection Law is basically motivated by consumers and business actors who in practice are not balanced. In the case of business actors' responsibilities, it is necessary to see whether there is a loss suffered by consumers as a result of the use, use and use of products produced by certain business actors. Keyword : legal liability, misleading advertising, business actors